Selenium Flux Effect on Cu(In, Ga)Se2 Thin Films Grown by a 3‐stage Co‐evaporation Process. Issue 10 (6th August 2015) - Gwak, Jihye; Lee, MinJi; Yun, Jae Ho; Ahn, SeJin; Cho, Ara; Ahn, SeungKyu; Hulme, John P.; Shin, Kee Shik; Yoon, Kyung Hoon
Abstract An investigation into the effects of Se flux on absorber thin film growth at each step of a 3‐stage co‐evaporation process was conducted to further optimize the performance of CIGS solar cells. In 'step I' forming an In‐Ga‐Se precursor thin film during the 3‐stage process, Se flux affected the preferred orientation of the CIGS crystal structure, but not the film morphology. In 'step II', no correlation was found between Se flux and the crystal structure, although excessively high Se flux employed throughout the 3‐stage process degraded the solar cell performance. A CIGS thin film, with a (220/204) crystal orientation, minor physical surface defects and ∼20 nm thick MoSe2 at CIGS/Mo interface, was obtained by fine control of Se flux conditions (high Se flux at 'step I' and low Se flux at 'step II') at optimum substrate temperatures. The solar cell fabricated using the aforementioned CIGS thin film showed the highest conversion efficiency of 20.02 %.